INFLUENCE OF VIDEO GAMES ON THE ACQUISITION OF THE ENGLISH LANGUAGE - Muhammad Dhany Winaldo; Lulud Oktaviani (fsip.teknokrat.ac.id, 2022)
The number of schoolchildren fluent in English has increased significantly over the past decade. The amount of English lessons per week is one explanation, but media influence is perhaps even more important. Video games are massively marketed to college students. In this study, a survey was conducted to examine the relationship between playing video games and English proficiency. Many students responded to the survey. This included a range of questions about how often and how well video games are played. Researcherss have concluded that video games have a significant impact on language acquisition. Vocabulary and pronunciation were the most helpful areas. Video games are a highly rewarding pastime and create a comfortable and stimulating environment perfect for learning a foreign language.